Correlation Between Complexity of Coronary Lesions and Delta High-sensitivity Troponin (hs-cTn) I Levels in Patients of Non-ST Elevation Myocardial Infarction : Complexity of Coronary Lesions and Delta High-sensitivity Troponin I in Non-ST Elevation Myocardial Infarction - Azam, Muhammad Hammad; Wahab, Muhammad Abdul; Danish, Naveed; Taha, Muhammad; Naeem, Shitba; Muhammad, Shaheer Khan (Pakistan Journal of Health Sciences, 2024)
Non-ST Elevation Myocardial Infarction is a critical condition where early identification of myocardial injury is essential for risk stratification and treatment. High-sensitivity cardiac troponin I (hs-cTnI) is a well-established biomarker for detecting myocardial damage. Objectives: To assess the association between Syntax scores and initial significant delta hs-cTnI in patients who had been hospitalized with Non-ST Elevation Myocardial Infarction. Methods: Observational cohort study from January 2022 to December 2022 involving a total of one hundred and fifty patients admitted at Hayatabad Medical Complex Peshawar. hs-cTnI on admission and at 1, 2 hours and between (6h-12 h) post-admission daily was measured. Coronary lesion complexity was assessed with Syntax scores according to the results of coronary angiography. Statistical Analysis of data was performed using Pearson correlation to analyze the association between syntax scores delta hs-cTnI levels. Results: SYNTAX scores were correlated with Δhs-cTnI levels at all-time points, and the strongest correlation was found 6-12 hours post-admission (r=0.78). The syntax score had a mean value of 24.11 ± 14.74, and hs-cTnI levels increased over time to reflect the extent of myocardial injury. Conclusions: It was concluded that in Non-ST Elevation Myocardial Infarction patients, Syntax scores demonstrating more complex coronary lesions are related to higher delta hs-cTnI levels. This value highlights the use of hs-cTnI as a biomarker to evaluate the severity of myocardial injury and direct clinical decision-making in Non-ST Elevation Myocardial Infarction. Delta hs-cTnI measurements in diagnostic and risk stratification algorithms may lead to enhanced early identification of disease with improved outcomes.